StoreApp: A Fault Injection Testing Tool for Software Using Web Service - Deher, Rajbir Singh (My University, 2014)
Fault injection is a phrase covering a variety of techniques for inducing faults in systems to measure their response to those faults. In particular, it can be used in both electronic hardware systems and software systems to measure the fault tolerance of the system. For hardware, faults can be injected into simulations of the system, as well as into implementation, both on a pin or external level and, recently, on an internal level for some chips. For software, faults can be injected into simulations of software systems, such as distributed systems, or into running software systems, at levels from the CPU registers to memory to disk to networks. Fault injection is best used as a means for measuring the fault tolerance or robustness of a system, especially for stress testing a system that may experience faults too infrequently for normal testing. While the theory behind fault injection is still being developed, the mechanisms are well understood. For an embedded system designer attempting to measure the degree to which his design is resistant to faults, fault injection can be a useful technique for quantifying this aspect of design.
MT, SMCA
Keywords: Fault; Software Testing